Usage of natural and chemically treated sugar cane bagasse as adsorbent material for adsorption of Cu2+ - Cascaret-Carmenaty, Dannis Adrian; Rodríguez-Matos, Josefina; Ricardo-Lobaina, Carlos Alfredo; Quesada-González, Omaida; Bahín-Deroncelé, Leonardo (Revista Cubana de Química, 2020)
This research evaluates the adsorption of Cu2+ by sugarcane bagasse, both natural and treated with NaOH and H3PO4, in water samples from "Blue Lagoon" of El Cobre, Santiago de Cuba. Experiments showed that natural bagasse is capable of removing 31, 6% of Cu2+ in standard solutions at pH = 3,30, contact time 30 minutes and ratio of 0,50 g (mass of adsorbent) / 50 mL. The removal percentages of bagasse treated with NaOH and H3PO4 were 39.3% and 93,3 % respectively, for the same experimental conditions. In the real matrix, the copper removal percentages were 18,34; 29,4 and 86,5% respectively. According to Langmuir’s model, the measured maximum adsorption capacity (qm) was 7,57 mg / g at pH = 3,30 with r2 = 0,96. The evidence suggests a strong potential for bagasse as an adsorbent material, as well as an alternative treatment to minimize the impact of pollution by Cu2+ on aquatic ecosystems.